ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITASLAPORAN KEUANGAN PADA PERUSAHAAN PERBANKAN - Ni Luh Gde Novitasari; Ni Wayan Juli Martani (Journal of Applied Management and Accounting Science, 2022)
This study aims to analyze that effect of audit quality, firm size, earnings management, financial distress and audit committee on integrity of the financial statements. Thisstudy is located in banking companies listed on the Indonesia Stock Exchange during 2018-2020. By using purposive sampling, this study resulting 23 companies and 69 research observation as a sample. Research data was analyzed by using multiple linear regression analysis. The results of this study show that auditquality has a positive effect on the integrity of financial statements, financial distress has a negative effect on the integrity of financial statements, while company size, earnings managementand audit committee have no effect on the integrity of financial statements.